2018
DOI: 10.1155/2018/9078537
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Chemotherapy Downstaged Oral Squamous Cell Carcinoma from Nonresectable to Resectable in a Rescue Dog: Diagnosis, Treatment, and Outcome

Abstract: This case report documents the diagnosis, treatment, and outcome of a nonresectable oral squamous cell carcinoma in a dog with initial poor prognosis. An approximately 4-year-old female Staffordshire Bull Terrier presented with a large mass on the front of lower jaw which was diagnosed as oral papillary squamous cell carcinoma by histopathology. CT scans revealed invasion of the cancer to the frenulum of the tongue. The mass was inoperable due to location, expansiveness, and metastatic lymph nodes. The dog rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Based on our experience with carrier-based Pt­(II) drugs, we hypothesized that localized delivery to tumor would further improve the activity of Pt­(IV). In addition, we believed a HA-based carrier could increase retention and tumor-associated lymph node uptake, while lessening RBC inactivation, a drawback of previous unsuccessful Pt­(IV) molecules including the clinically investigated drug sartaplatin. , The uniqueness of the HA-Pt­(IV) formulation in this work is manifested by the combination of at least three factors including - a lipophilic platinum­(IV) and its immunological properties as discussed below, a safe and pharmacokinetically tailored HA-based drug carrier demonstrated by previous animal studies, ,,, and a clinically feasible mode of intralesional delivery for spontaneous cancers based on the results of canine clinical trials. ,, The HA-Pt­(IV) formulation uses FDA-designated generally recognized as safe substances such as α-tocopherol, and biodegradable and biocompatible natural polysaccharide such as hyaluronic acid, which has been approved by the FDA for use as a dermal filler and as an intra-articular injection. These characteristics render HA-Pt­(IV) a clinically relevant molecule and justify the synthetic and testing efforts, which are discussed below in detail.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Based on our experience with carrier-based Pt­(II) drugs, we hypothesized that localized delivery to tumor would further improve the activity of Pt­(IV). In addition, we believed a HA-based carrier could increase retention and tumor-associated lymph node uptake, while lessening RBC inactivation, a drawback of previous unsuccessful Pt­(IV) molecules including the clinically investigated drug sartaplatin. , The uniqueness of the HA-Pt­(IV) formulation in this work is manifested by the combination of at least three factors including - a lipophilic platinum­(IV) and its immunological properties as discussed below, a safe and pharmacokinetically tailored HA-based drug carrier demonstrated by previous animal studies, ,,, and a clinically feasible mode of intralesional delivery for spontaneous cancers based on the results of canine clinical trials. ,, The HA-Pt­(IV) formulation uses FDA-designated generally recognized as safe substances such as α-tocopherol, and biodegradable and biocompatible natural polysaccharide such as hyaluronic acid, which has been approved by the FDA for use as a dermal filler and as an intra-articular injection. These characteristics render HA-Pt­(IV) a clinically relevant molecule and justify the synthetic and testing efforts, which are discussed below in detail.…”
Section: Resultsmentioning
confidence: 57%
“…43,44 The uniqueness of the HA-Pt(IV) formulation in this work is manifested by the combination of at least three factors including -a lipophilic platinum(IV) and its immunological properties as discussed below, a safe and pharmacokinetically tailored HA-based drug carrier demonstrated by previous animal studies, 7−9,11,13,45−47 and a clinically feasible mode of intralesional delivery for spontaneous cancers based on the results of canine clinical trials. 10,14,15 The HA-Pt(IV) formulation uses FDA-designated generally recognized as safe substances such as α-tocopherol, and biodegradable and biocompatible natural polysaccharide such as hyaluronic acid, which has been approved by the FDA for use as a dermal filler and as an intra-articular injection. These characteristics render HA-Pt(IV) a clinically relevant molecule and justify the synthetic and testing efforts, which are discussed below in detail.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results confirmed that 23% of the animals had a complete regression of the disease, while 15% had a partial response [ 92 ]. Recently, Cai et al developed a cisplatin-hyaluronan nanoconjugate (HylaPlat) with the aim of treating a dog with a non-resectable oral squamous cell carcinoma with metastases in the local lymph nodes [ 97 ]. The dog was treated with 5–10 mg/m 2 of HylaPlat intra-lesionally injected every three weeks, for a total of four times.…”
Section: Drug Delivery Systems For the Treatment Of Canine Tumorsmentioning
confidence: 99%
“…In addition, the drug delivery system promoted the localization of cisplatin within the metastatic lymph nodes [ 98 ]. The dog reached a complete remission and maintained a stable condition for at least one year after the treatment ( Figure 3 ) [ 97 ].…”
Section: Drug Delivery Systems For the Treatment Of Canine Tumorsmentioning
confidence: 99%